EFL STUDENTS’ CHALLENGES IN WRITING RESEARCH PROPOSALS - Gai Mali, Yustinus Calvin (LLT Journal: A Journal on Language and Language Teaching, 2023)
This qualitative study delves closely into students’ challenges of writing specific sections (i.e., introduction, literature review, and method) of their research proposal and coping strategies to deal with those challenges, specifically in online learning environments amidst the Covid-19 pandemic. Data were garnered from six Indonesian EFL undergraduates taking a research design course at a private university in Central Java, Indonesia. Selected based on the intensity sampling technique, these students were involved in an in-depth semi-structured interview session with the researcher to share their voices on the writing challenges and coping strategies as well as parts of the course they found useful and practical suggestions for class improvement. The data analysis results indicated that writing a good research proposal might be challenging for the research participants, considering the various challenges they experienced when writing sections of their research proposal. Different coping strategies to deal with those challenges, useful parts of the course and suggestions for class improvement were presented and discussed in the discourse of the reviewed literature. The paper ends with some directions for future research.